2012
DOI: 10.1080/08946566.2012.661672
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Definitions of Financial Abuse in Elderly Korean Immigrants: The Contribution of Traditional Cultural Values

Abstract: The purpose of this study is to explore the cultural definitions of financial abuse from the perspective of 124 elderly Korean immigrants and to examine the role of traditional cultural values in their definitions by using a mixed methods approach. The qualitative analysis generated four themes relevant to definition of financial abuse. A binary logistic regression indicated that those with stronger cultural adherence to traditional values had higher odds of providing culture-based definitions of financial abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This finding was corroborated by Lee et al's (2012) study, which found a similar definition of financial abuse among elderly Korean American immigrants. In contrast to the shared formal concept of financial abuse in Western countries, including the United States, financial abuse defined by Korean elders is based on filial piety.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding was corroborated by Lee et al's (2012) study, which found a similar definition of financial abuse among elderly Korean American immigrants. In contrast to the shared formal concept of financial abuse in Western countries, including the United States, financial abuse defined by Korean elders is based on filial piety.…”
Section: Discussionsupporting
confidence: 90%
“…This concern is particularly salient in light of studies that have shown that understandings, perceptions, and attitudes toward financial abuse vary among people from different ethnic and cultural backgrounds in the United States, including Korean American immigrants (Chang & Moon, 1997;Lee & Eaton, 2009;Lee et al, 2012;Moon et al, 2001;Moon & Williams, 1993;Pablo & Braun, 1997). For example, a vast majority of elderly Korean American immigrants defined financial abuse as "no provision of financial assistance to elderly parents" (Lee et al, 2012, p. 298), a culturally informed sentiment that is not reflected in formal definitions of financial abuse in the United States (NCEA, 1998).…”
Section: One Of the Critical Issues In Addressing Financial Abuse In mentioning
confidence: 97%
See 3 more Smart Citations